METHODS OF DEVELOPING INTERACTIVE ABILITIES OF MORAL AND AESTHETIC COMPETENCE OF FUTURE TEACHERS (Scientific journal of the Fergana State University, 2025)
In this article, in the methodology for developing the moral and aesthetic competence of future teachers, the main function of the teacher is to educate, train and form a person. The education of a person as a person with high spirituality is considered a basic concept in pedagogy and means the joint priority activity of the family and society aimed at the formation of a harmonious personality. It is envisaged to determine the spiritual aspects of the human personality with the help of education. It is studied that the transformation of worldview, beliefs, virtue, beauty, goodness, and justice into personal qualities is possible only with the help of education.